2003
DOI: 10.1097/00000542-200304000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetic Requirements Are Greater in Dystocia Than in Normal Labor

Abstract: These data suggest that an increased local anesthetic requirement for epidural labor analgesia is associated with more intense pain related to dystocia. Women in early, clinically normal labor but who later develop dystocia require more local anesthetic and, by inference, are experiencing more severe pain than women who deliver vaginally. This association should be considered when studying the relation between the method of labor analgesia and the course of labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 14 publications
0
39
0
5
Order By: Relevance
“…Individual patient outcomes were categorized as success, failure, or rejection, similar to previous minimal local analgesic concentration (MLAC) [12] and minimal analgesic dose (MAD) [33] methodologies. The MLAC methodology has been extensively used in obstetric anesthesia investigations to assess differences in potencies and analgesic responses both to opioids and local anesthetics [1,6,12,13,31,[36][37][38]39,40,41]. We used the same criteria to define successful analgesia or failure as those used in previous studies assessing median effective doses of opioids or local anesthetics, as indicated below:…”
Section: Initial Sequential Allocation Studymentioning
confidence: 99%
“…Individual patient outcomes were categorized as success, failure, or rejection, similar to previous minimal local analgesic concentration (MLAC) [12] and minimal analgesic dose (MAD) [33] methodologies. The MLAC methodology has been extensively used in obstetric anesthesia investigations to assess differences in potencies and analgesic responses both to opioids and local anesthetics [1,6,12,13,31,[36][37][38]39,40,41]. We used the same criteria to define successful analgesia or failure as those used in previous studies assessing median effective doses of opioids or local anesthetics, as indicated below:…”
Section: Initial Sequential Allocation Studymentioning
confidence: 99%
“…4 Increased analgesic requirements have been demonstrated to be associated with dysfunctional labor, although it is unlikely that the dysfunctional labor was caused by the epidural per se. 6 Other investigators have found that fetal head malposition did not differ in parturients with and without neuraxial analgesia when stratified by mode of delivery. 7 There are multiple limitations of our study design and conclusions.…”
Section: Discussionmentioning
confidence: 93%
“…Dystocia leading to caesarean section is associated with increased local anaesthetic requirements in early labour. 34 Similarly, progression of labour significantly increases local anaesthetic requirements assessed by the MLAC methodology. 35 Inversely, obese patients have been demonstrated to have lower local anaesthetic requirements for epidural analgesia in labour.…”
Section: Obstetric Conditionsmentioning
confidence: 99%